BEDE. - BROWN, GEORGE. ([S.l.])
1 online resource
Keywords: Bede is the inaugural volume in the Sources of Anglo-Saxon Literary Culture series, which seeks to comprehensively map British literary culture from 500 to 1100 CE. This volume presents four texts, or fascicles, dedicated to the Venerable Bede (d. 735), theologian and author of the Historia ecclesiastica gentis Anglorum. Articles provide a wealth of information on Bede through manuscript evidence, medieval library catalogs, citations, and quotations. Using discussions of source relationships, the entries weigh and consider different interpretations of Bede's works and suggest possibilities for future research. Part of an exciting new reference series, this book"and those that follow"will be indispensable to anyone interested in the history and literature of the period.